Comparative Export Competitiveness of Green Beans and Instant Coffee: Evidence from Vietnam and China - Chen, Hong; Pham, Thanh Lam (International Journal of Economics and Financial Issues, 2026)
According to the types of two kinds of coffee products, which are green coffee (HS 0901.11) and instant coffee (HS 2101.11), this study will compare Vietnam’s and China’s export competitiveness from 2005 to 2023. Using trade performance indicators such as Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA) and Trade Balance Index (TBI); It can be known that their degrees of competitive advantage, export specialisation and the development trend of long-term competitiveness show considerable differences. According to the data presented above, it can be concluded that Vietnam has kept a strong comparative advantage in terms of green coffee export business; meanwhile, under the drive of enhanced processing capacity and upgraded value chains, its participation rate for instant coffee products has also increased continuously. On the other hand, China’s imports continue to grow rapidly, and it is still in a phase where imports exceed exports; therefore, our competitiveness index has not yet turned positive, and there is no apparent export advantage. Based on the above results, it can be known that the two coffee industries have different development paths and provide empirical support for how structural factors and the direction of the domestic market affect the competitiveness of the industry.